2006
DOI: 10.1007/s00267-005-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Land Use/Land Cover Change in the Buffer Zone of a National Park in the Tropical Andes

Abstract: The impacts of land use and land cover (LULC) change in buffer zones surrounding protected ecological reserves have important implications for the management and conservation of these protected areas. This study examines the spatial and temporal patterns of LULC change along the boundary of Rio Abiseo National Park in the Northern Peruvian Andes. Landscape change within four ecological zones was evaluated based on trends expected to occur between 1987 and 2001. Landsat TM and ETM imagery were used to produce L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 52 publications
1
50
0
5
Order By: Relevance
“…Small habitat patches have significant edge effect, while isolated patches have reduced gene flow and increased rates of local population extinctions. The amount of core forest habitat and the shape of forest patches change as human populations increase and land use intensifies (Kintz et al, 2006), thus likely also reducing population sizes of species requiring large core habitats (e.g., Ewers & Didham, 2006). The rate, type, and location of habitat change in relation to intrinsic population increases of the species of concern are parameters involved in the likelihood of local extinctions (Schrott et al, 2005).…”
Section: Future Geographies Of the Andes: Toward A Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Small habitat patches have significant edge effect, while isolated patches have reduced gene flow and increased rates of local population extinctions. The amount of core forest habitat and the shape of forest patches change as human populations increase and land use intensifies (Kintz et al, 2006), thus likely also reducing population sizes of species requiring large core habitats (e.g., Ewers & Didham, 2006). The rate, type, and location of habitat change in relation to intrinsic population increases of the species of concern are parameters involved in the likelihood of local extinctions (Schrott et al, 2005).…”
Section: Future Geographies Of the Andes: Toward A Conceptual Modelmentioning
confidence: 99%
“…Land change science draws on a wide range of social, biological, and physical sciences for paradigms and explanations (Gutman et al, 2004). Kintz et al (2006) used this approach to map and quantify change in landscape mosaics of northern Peru over a 13-year period. Most change was related to altered land use as local population size doubled with in-migration.…”
Section: Humanized Landscapes Of the Andesmentioning
confidence: 99%
“…Scholes and Breeman [3] indicated that in addition to fossil fuels, the conversion of natural vegetation to agriculture is partially responsible for changes in the atmospheric composition and climate conditions. Despite the importance of landscape conversion to fulfill basic needs of humankind, LCCs such as deforestation have been recognized as major problems in the world and are drivers of global warming [4,5], which result in negative consequences for life on earth.…”
Section: Introductionmentioning
confidence: 99%
“…In tropical mountains, increases in woody plant coverage were reported based on Landsat satellite images by Kintz et al (2006) and Lipton (2008), with studies of seedling establishment in the timberline zone by Rehm and Feeley (2013), and in mapping done using MODIS data by Aide et al (2013), who report many dry and steep areas with expanding or regrowing forests or shrublands. These changes are those expected globally, and are also those found in the modeling done by Tovar et al (2013), who predict shifts in ecological zones, with more area in the tropical Andes with montane shrublands and seasonally dry forest.…”
Section: Dynamics Of Woody Plantsmentioning
confidence: 94%